Pengaruh Media Alphabet Card terhadap Keterampilan Membaca Siswa Kelas 2 Sekolah Dasar - Rustam, Ahmad; Wulastri, Lana; Puteri, Sri Marlia (Arden Jaya Publisher, 2024)
The purpose of this study was to determine the effect of Alphabed Card media on reading skills of second grade students in elementary school. This research is quantitative research with experimental method using pre-experimental with 0ne group pretest and posttest design. This research will conduct randomly, where a randomized design is called a randomized experimental design. The results obtained can be said that there is an influence of the alphabet card media on the reading skills of students, this is proven by the results of the acquisition of students' scores for individual mastery on the pretest test of 65.33, while the post-test 88.67. The results of the normality test in the pretest 0.184 and the result of post test were obtained at 0.200, which was greater than the specified alpha value, which was 5% (0.05). The homogeneity test results obtained that the significance value was 0.569. therefore in accordance with a> 0.05, it can be said that the data is accepted or homogeneous on both tests, namely pretest and posttest. From the results of the hypothesis test obtained a sig value of 0,000 which is smaller than 0.05 alpha. Thus, the results obtained, that there is an influence of alphabet card media on reading skills in grade 2 elementary school, using the media can help students in the learning process.